An outlook on mechanisms inciting drought tolerance in cotton (Gossypium hirsutum) - MANJU, S; RAJESWARI, S; BOOPATHI, N MANIKANDA; PREMALATHA, N; SRITHARAN, N; UMA, D (The Indian Journal of Agricultural Sciences, 2025)
Drought is a multifaceted abiotic stress that affects plants at morphological, physiological, biochemical, and molecular levels. In the face of increasing climate variability, plants exhibit diverse growth and reproductive responses to water scarcity. Cotton, a globally significant fibre crop with substantial economic value, is particularly vulnerable to drought during key developmental stages. Tolerance to drought in cotton involves a suite of physiological responses, including maintenance of relative water content, leaf water potential, stomatal conductance, and osmotic adjustment. Biochemically, the scavenging of reactive oxygen species (ROS) through antioxidant enzymes and the activation of stress-responsive phytohormones such as abscisic acid play vital roles in plant survival. At the molecular level, drought tolerance is enhanced by the upregulation of genes such as GhSP1, GhFTL1, GhEXLB2, and GhGLK1, alongside the downregulation of MAPKKK genes. Conversely, overexpression of GhWRKY6 may induce ROS-mediated oxidative damage. Emerging studies highlight the importance of transcription factors like GhirNAC2 and the regulatory influence of miR394a/b on GhD01G0229 under drought stress. Mapping and functional characterization of these genes, transcription factors, and miRNAs provide valuable insights into the genetic architecture of drought tolerance and offer potential targets for crop improvement. This review explores the integrated physiological, biochemical, and molecular mechanisms that confer drought resilience in cotton